Obtenção de estruturas auto-montadas de oxihaletos de bismuto e investigação das suas propriedades ópticas e catalíticas - LIMA, Gênesis de Oliveira (2018)
In this work was obtained nanostructured bismuth oxyhalides by different methods, which it was characterized using X-ray diffraction (XRD), scanning electronic microscopy (SEM), Raman spectroscopy, Fourier-transform infrared (FTIR), and diffuse reflectance spectroscopy (DRS). Both methods have shown efficiency in the obtaining of nanostructures with high crystallinity, which was proved for XRD and Raman spectroscopy. Though, the pattern XRD have shown different profiles the SEM images have shown few changes to morphology found out. The photoluminescence measure to Bi1-xAgxOCl nanocrystals shown intensity different with the increase of Ag+ dopping. Similarly, BiOBr nanocrystal obtained with templates, different photoluminescence intensity was observed. In both cases, this suggests structural changes during the synthesis process. The investigation of photocatalytic activity using RhB as a model of the contaminant has shown that BiOBr nanocrystals have a better photocatalytic activity than Bi1-xAgxOCl nanocrystals. The photocatalysis using BiOBr, degraded 98 % of RhB dye (in solution) at 40 min using irradiation UV-Vis, which presented a kinetic constant k = 0.1227 cm-1. The Bi0.96Ag0.04OCl nanocrystals presented a slightly less photodegradation rate to same conditions used to BiOBr photocatalyst. It degraded 96 % at 40 min, with kinetic constant k = 0.0971 cm-1. The synthesis methods used to obtain BiOBr and Bi1-xAgxOCl shown to be able to make structural changes, which have been proved for photoluminescence measures, but few amount defects still are present in the structure, which contributes to loss of photocatalytic efficient. Therefore, the nanoparticles obtained by microwave assisted hydrothermal showed efficient for photocatalytic applications in the degradation of organic dye Rh B in aqueous solution when irradiated by UV-Vis